2005
DOI: 10.1136/bmj.38467.485671.e0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of studies of the timing of tracheostomy in adult patients undergoing artificial ventilation

Abstract: Objective To compare outcomes in critically ill patients undergoing artificial ventilation who received a tracheostomy early or late in their treatment. Data sources The Cochrane Central Register of Clinical Trials, Medline, Embase, CINAHL, the National Research Register, the NHS Trusts Clinical Trials Register, the Medical Research Council UK database, the NHS Research and Development Health Technology Assessment Programme, the British Heart Foundation database, citation review of relevant primary and review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
337
1
34

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 558 publications
(386 citation statements)
references
References 28 publications
14
337
1
34
Order By: Relevance
“…Early tracheostomy resulted in a decreased risk of mortality and increased weaning success in some studies (36)(37)(38). In contrast, early tracheostomy did not significantly alter the mortality rate or the duration of MV in other studies (39,40). In the present study, the interval from intubation to tracheostomy did not significantly differ between the weaning success and failure groups (a median day of 16 days vs. 15 days; P=0.725).…”
Section: Discussionmentioning
confidence: 30%
“…Early tracheostomy resulted in a decreased risk of mortality and increased weaning success in some studies (36)(37)(38). In contrast, early tracheostomy did not significantly alter the mortality rate or the duration of MV in other studies (39,40). In the present study, the interval from intubation to tracheostomy did not significantly differ between the weaning success and failure groups (a median day of 16 days vs. 15 days; P=0.725).…”
Section: Discussionmentioning
confidence: 30%
“…67,68 Their conclusion was that, despite considerable methodologic heterogeneity, an early tracheostomy strategy was associated with trends in favor of early tracheostomy in mortality (49% vs 64%) and pneumonia (12% vs 22%), as well as a significant reduction in time on ventilator in favor of early tracheostomy (7 d vs 17 d).…”
Section: The Role Of Tracheostomiesmentioning
confidence: 99%
“…However, all of these studies demonstrated either benefit or null effect for early tracheostomy, and none demonstrated detrimental effects. 50 There were major differences in the specific tracheostomy timing (early vs late) and the patient populations (medical critically ill, surgical critically ill, burn injury, head injury subjects) in these 4 studies, and no standard ventilator weaning protocol was used, making ventilator duration and ICU stay outcomes vulnerable to clinical practices in these ICUs.…”
Section: Observational Studiesmentioning
confidence: 99%